Ten Days of Intermittent, Low-dose Carbon Monoxide Inhalation does not Significantly Alter Hemoglobin Mass, Aerobic Performance Predictors, or Peak-power Exercise Tolerance - Ryan, B. J.; Goodrich, J. A.; Schmidt, W.; Kane, L. A.; Byrnes, W. C. (International Journal of Sports Medicine, 2016)
Carbon monoxide (CO) rebreathing procedures are used to assess hemoglobin mass (Hbmass) but recent evidence suggests that CO is a signaling molecule that may alter physiological functions. We examined the effects of 10 days of intermittent, low-dose CO inhalation on Hbmass, aerobic performance predictors, and peak-power exercise tolerance. 18 recreationally-active men were randomized to either CO or placebo inhalation groups in a single-blind, pre-post parallel-groups trial. Primary outcomes were assessed before and after an intervention period during which subjects inhaled a bolus of 1.2 ml kg−1 CO or placebo (room air) for 30 s, once per day on 10 days over a 12-day period. Cycling tests were performed >16 h following CO inhalation to exclude acute effects of CO exposure. CO inhalation elevated carboxyhemoglobin by 4.4±0.4% (mean±SD) following each exposure. Compared to placebo, chronic CO inhalation did not significantly alter Hbmass (p=0.99), peak oxygen uptake (p=0.59), peak power output (p=0.10), submaximal oxygen uptake (p=0.91), submaximal RER (p=0.22), lactate threshold (p=0.65), or peak-power exercise tolerance (p=0.60). In conclusion, our data support the ability to perform repeated measurements of Hbmass using CO rebreathing over a 12-day period without altering physiological responses.
Keywords: carboxyhemoglobin; exercise testing; gasotransmitter